Preparation of an Amperometric Glucose Biosensor on Polyaniline-Coated Graphite. (29th January 2021) - Neupane, Shova; Bhusal, Suresh; Subedi, Vivek; Nakarmi, Krishna Badan; Gupta, Dipak Kumar; Yadav, Ram Jeewan; Yadav, Amar Prasad
Abstract : Control of glucose concentration has tremendous significance in medical diagnosis, pharmaceuticals, food, and fermentation industries. Herein, we report on the fabrication of a facile, low-cost, and sensitive enzyme-based amperometric sensor using the electrochemically deposited polyaniline (PANI) film on a graphite electrode. PANI was deposited from an aqueous solution of 0.2 M aniline in 1.0 M hydrocholoric acid (HCl) by cyclic voltammetry (CV). Surface morphology and composition characterization of the PANI film were carried out by scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), and Fourier-transform infrared (FTIR) spectroscopy. Potentiostatic immobilization of glucose oxidase (GOX ) enzyme in the PANI film was carried out at 0.75 V to fabricate an amperometric glucose biosensor (GOx/PANI/graphite biosensor). The glucose concentration response of the prepared sensor was studied amperometrically by detecting hydrogen peroxide (H2 O2 ). The detection of H2 O2 was optimized by calibrating the effects of pH, reduction potential, and background current. A reduction potential of -0.4 V at pH 6 was the best combination to get a maximum amperometric response of the GOx/PANI/graphite biosensor. A stable current response was obtained in 4 min with a high reproducibility in linearity within the concentration range of 0.01 M-0.1 M D-glucose. Therefore, the fabricated GOx/PANI/graphite biosensor could be a promising candidate for glucose sensing.